Mucosal invariant T cells combined with inflammatory cytokines were used to identify chronic rhinosinusitis with nasal polyps or without nasal polyps - Wang, Yilong; Feng, Yongjun; Song, Jie; Mou, Zhonglin (Journal of Medical Biochemistry, 2025)
Objective: The present study attempted to analyze the effect of mucosal-associated invariant T (MAIT) combined with inflammatory factors in identifying chronic rhinosinusitis (CRS) without nasal polyps (CRSsNP) and CRS with nasal polyps (CRSwNP) that provides a clinical reference.Methods: In this retrospective study, we enrolled 56 CRSsNP patients, 68 CRSwNP patients, and 60 healthy controls. Flow cytometry was used to detect the frequency of peripheral blood MAIT cells (MAIT+). Serum levels of hs-CRP, IL-1β, and IL-6 were measured by ELISA and automatic blood cell analyzer, and their correlations with MAIT cell alterations were analyzed. The diagnostic effect of MAIT+ combined with hs-CRP, IL-1β, and IL-6 on CRS was analyzed using ROC curves.Results: Both CRSsNP and CRSwNP patients exhibited significantly reduced MAIT+ frequencies compared to controls (P